On the exact sequences of FW6- pair of hooks representation modules over a field of characteristic 0 (Journal of the College of Basic Education, 2019)
The intention of this paper is to find the exact and split sequences of the sub modules of FW6-second and third pair of hooks representation modules, when F be a field of characteristic 0 . This intention is revealing by presenting the main results theorems (3-1) and (3-2), where we gave two of this kind of sequences.0 0Here we refer that depending on the structural constructing of the elements (modules) of these sequences or it‘s sub modules by counting the dimensions was essential for proving these theorems.